An application of polyamide membrane based on iron acetylacetonate
Through the use of acetyol iron iron as an oil phase additive during the preparation of the reverse osmosis membrane, the cross -linking degree and micro -nanoidal porosity structure of the polyamide membrane are added to solve the problem of the existing reverse osmosis membrane's low interception rate of organic micro -pollutants. A more efficient water treatment effect is achieved.
Patent Information
- Application Number
- CN202211667345.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-12-23
AI Technical Summary
The existing reverse osmosis membrane has a low retention rate of neutral and hydrophobic organic micropollutants, which affects its application effect in water treatment.
The acetone iron is used as an oil phase additive to increase the cross -linking of polyamide membrane through the interface polymerization reaction to regulate its micro -pore structure, thereby increasing the cutting rate of organic micro -pollutants.
It significantly improves the interception rate of organic micro -pollutants, improves the pollution efficiency during the water treatment process, while maintaining the surface and roughness of the membrane unchanged.
Smart Images

Figure CN115970503B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite reverse osmosis membrane preparation and relates to an application of a polyamide membrane based on ferric acetylacetonate. Background Art
[0002] As a new and efficient chemical separation technology in contemporary times, membrane separation technology plays an important role in solving the water resource crisis. Reverse osmosis membrane is an effective separation method used in water treatment processes. Compared with traditional thermal desalination technology, it has the advantages of no phase change in the separation process, high separation efficiency, small footprint, and simple operation. It has been widely used in seawater / brackish water desalination, ultrapure water preparation, secondary industrial wastewater recovery, food concentration and other fields. At present, commercial nanofiltration and reverse osmosis membranes are mostly composite membranes, usually composed of three parts: a non-woven reinforcement layer, a polymer support layer and a polyamide separation layer. Interfacial polymerization is a commonly used method for preparing composite nanofiltration / reverse osmosis membranes, which has the advantages of simple operation, easy control and scalability.
[0003] At present, the most widely used reverse osmosis membrane is an aromatic polyamide thin-layer composite reverse osmosis membrane (referred to as polyamide reverse osmosis membrane) prepared by interfacial polymerization. Polyamide reverse osmosis membranes can remove most pollutants in wastewater, but they often show low retention rates for neutral and hydrophobic organic micropollutants (such as endocrine disrupting compounds (EDC)). Many of these pollutants are toxic and harmful to human health and the aquatic environment. Although the polyamide layer of the reverse osmosis membrane prepared by interfacial polymerization has dense pores, according to literature research, some macromolecules and nanoparticles can penetrate the reverse osmosis membrane. The reason may be that the cross-linking degree of the polyamide layer is not high enough, which affects the network pores of the polyamide, making the polyamide reverse osmosis membrane poor in retaining organic micropollutants. Summary of the invention
[0004] The purpose of the present invention is to overcome the disadvantages of the prior art and provide an application of a polyamide membrane based on ferric acetylacetonate to solve the problem of low retention rate of organic micropollutants.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] An application of a polyamide membrane based on ferric acetylacetonate, wherein the polyamide membrane based on ferric acetylacetonate is used for removing organic micropollutants;
[0007] The preparation process of the ferric acetylacetonate polyamide film comprises the following steps:
[0008] Step 1, soaking the basement membrane in an aqueous solution to form a basement membrane 1;
[0009] Step 2, immersing the process base film 1 in an organic phase solution to cause an interfacial polymerization reaction to form a process base film 2; the organic phase solution is composed of 10% dichloromethane and 90% n-heptane solution by mass fraction, and trimesoyl chloride and ferric acetylacetonate are also added to the organic phase solution;
[0010] Step 3, cleaning the second process base film and then heat treating it to obtain a polyamide film.
[0011] Further improvements of the present invention:
[0012] Preferably, in step 1, the aqueous phase solution is a mixed solution containing camphorsulfonic acid, triethylamine and m-phenylenediamine.
[0013] Preferably, the mass fractions of camphorsulfonic acid, triethylamine and m-phenylenediamine in the aqueous phase solution are 2.6%, 1.1% and 3% respectively.
[0014] Preferably, in step 1, the basement membrane is immersed in the aqueous solution for 10 to 60 seconds.
[0015] Preferably, in step 2, 0.1 g of trimesoyl chloride is added to 100 mL of the organic phase solution.
[0016] Preferably, in step 2, 0.01 g to 0.06 g of ferric acetylacetonate is added to 100 mL of the organic phase solution.
[0017] Preferably, in step 2, the immersion time of the process base membrane 1 in the organic phase solution is 10 to 50 seconds.
[0018] Preferably, in step 3, the base film 2 is cleaned by an ethanol solution containing N-N-dimethylformamide.
[0019] Preferably, the heat treatment temperature is 60-100° C., and the heat treatment time is 3-7 min.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The invention discloses an application of a polyamide membrane based on ferric acetylacetonate, which uses the polyamide membrane for removing organic micropollutants. In the process of preparing the polyamide membrane, ferric acetylacetonate is used as an oil phase additive to prepare a method for removing organic micropollutants from the polyamide membrane. The invention adds ferric acetylacetonate to the oil phase, catalyzes the interfacial polymerization process, increases the cross-linking of m-phenylenediamine and trimesoyl chloride, and then regulates the micro-nano pores of the polyamide membrane, thereby improving the removal rate of organic micropollutants by the reverse osmosis membrane. Ferric acetylacetonate is tightly combined with polyamide, has no obvious cavities, does not affect the surface and roughness of the membrane, does not destroy the dense network structure of the polyamide, and can be evenly dispersed on the surface of the membrane, optimizing the permeability and selectivity of the reverse osmosis membrane. The main mechanism for removing organic micropollutants is the adsorption generated by size screening and specific interaction hydrogen bonds and π-π interactions. The high hydrophilicity of the membrane inhibits the interaction between the membrane and the solute, reduces the solute adsorption, thereby improving the interception rate. The preparation method is low in cost and easy to implement.
[0022] Furthermore, the prepared reverse osmosis membrane significantly improves the interception rate of organic micropollutants compared with ordinary membranes: under the test conditions of 200 μg / L ethylparaben aqueous solution, 15.5±0.1 bar and 25±1°C, the TOC and organic micropollutant interception rates can reach 1.61 mg / L and 88.90%, respectively. The present invention is not limited to the preparation of aromatic polyamide composite reverse osmosis membranes, but is also suitable for the preparation of other high-performance interfacial polymerization separation membranes. The micro-nano pores of polyamide will affect the separation performance of the reverse osmosis membrane and greatly reduce the interception rate. The present invention adds ferric acetylacetonate to the oil phase to increase the cross-linking of the polyamide membrane during interfacial polymerization, thereby improving the interception rate of the reverse osmosis membrane for organic micropollutants. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 : Scanning electron micrograph and atomic force micrograph of the polyamide composite reverse osmosis membrane prepared in Control Example 1; wherein (a) is a scanning electron micrograph, and (b) is an atomic force micrograph; it can be seen from the figure that the prepared reverse osmosis membrane has a typical ridge-valley structure.
[0024] Figure 2 : are scanning electron micrographs and atomic force micrographs of the polyamide composite reverse osmosis membrane obtained in Example 2; wherein, (a) is a scanning electron micrograph, and (b) is an atomic force micrograph; it can be seen from the figures that after the reverse osmosis membrane is activated, there is no significant difference between the membrane containing ferric acetylacetonate and the membrane not containing ferric acetylacetonate.
[0025] Figure 3: is a curve diagram showing the variation of the retention rate of the membranes prepared in Example 2, Example 4 and the comparative example over time. It can be seen from the figure that the performance of the membrane with ferric acetylacetonate added in the oil phase is significantly better than that of the ordinary membrane, and the membrane containing 0.03% ferric acetylacetonate has a higher retention rate. DETAILED DESCRIPTION
[0026] The present invention is further described in detail below in conjunction with the accompanying drawings:
[0027] In the description of the present invention, it should be noted that the orientations or positional relationships indicated by the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inside", "outside", etc. are based on the orientations or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention; the terms "first", "second", and "third" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance; in addition, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection or a detachable connection; it can be directly connected or indirectly connected through an intermediate medium, and it can be the internal communication of two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0028] The method of preparing a polyamide membrane for removing organic micropollutants by using ferric acetylacetonate as an oil phase additive of the present invention comprises the following steps:
[0029] 1) Immersing the base film in an aqueous solution containing camphorsulfonic acid, triethylamine and m-phenylenediamine for 10 to 60 seconds to allow the base film to be fully infiltrated by the aqueous solution; the mass fractions of camphorsulfonic acid, triethylamine and m-phenylenediamine in water are 2.6%, 1.1% and 3%, respectively.
[0030] 2) Immersing the membrane in an n-heptane solution (organic phase solution) containing dichloromethane, trimesoyl chloride, and ferric acetylacetonate for 10 to 50 seconds to initiate interfacial polymerization to form a polyamide separation layer; in terms of mass fraction, the organic phase solution is composed of 10% dichloromethane and 90% n-heptane solution, and 0.1 g of trimesoyl chloride and 0.01 g to 0.06 g of ferric acetylacetonate are also added to the organic phase solution;
[0031] 3) washing the membrane with an ethanol solution containing N-N-dimethylformamide;
[0032] 4) Then, the membrane is placed at 60-100° C. for heat treatment for 3-7 minutes to obtain an aromatic polyamide composite reverse osmosis membrane.
[0033] The following is further described in conjunction with specific embodiments.
[0034] Example 1
[0035] The surface of the base membrane was immersed in the aqueous solution for 60 seconds to allow the base membrane to be fully infiltrated by the aqueous solution. Subsequently, the solution was poured off. Next, after ensuring that there was no visible liquid on the membrane surface, the membrane surface was immersed in a 100 mL mixed solution containing 10 wt% dichloromethane and 90 wt% n-heptane solution for 30 seconds to initiate interfacial polymerization. 0.1 g of trimesoyl chloride and 0.01 g of ferric acetylacetonate were also added to the mixed solution. After interfacial polymerization, it was washed with 0.03% NN dimethylformamide ethanol solution. Finally, the membrane was heat treated at 80°C for 5 minutes to obtain an aromatic polyamide composite reverse osmosis membrane.
[0036] The TOC and rejection rate of the composite reverse osmosis membrane were tested by filtering a 200 μg / L aqueous solution of ethyl paraben at 15.5 bar and 25° C. to be 2.03 mg / L and 85.97%, respectively.
[0037] Example 2
[0038] The surface of the base membrane was immersed in the aqueous solution for 60 seconds to allow the base membrane to be fully infiltrated by the aqueous solution. Subsequently, the solution was poured off. Next, after ensuring that there was no visible liquid on the membrane surface, the membrane surface was immersed in a 100 mL mixed solution of 10 wt% dichloromethane and 90 wt% n-heptane solution for 30 seconds to initiate interfacial polymerization, to which 0.1 g of trimesoyl chloride and 0.03 g of ferric acetylacetonate were also added. After interfacial polymerization, it was washed with 0.03% NN dimethylformamide ethanol solution. Finally, the membrane was heat treated at 80°C for 5 minutes to obtain an aromatic polyamide composite reverse osmosis membrane.
[0039] The TOC and rejection rate of the composite reverse osmosis membrane were tested by filtering a 200 μg / L aqueous solution of ethyl paraben at 15.5 bar and 25° C. to be 1.61 mg / L and 88.90%, respectively.
[0040] Example 3
[0041] The surface of the base membrane was immersed in the aqueous solution for 60 seconds to allow the base membrane to be fully infiltrated by the aqueous solution. Subsequently, the solution was poured off. Next, after ensuring that there was no visible liquid on the membrane surface, the membrane surface was immersed in a 100 mL mixed solution of 10 wt% dichloromethane and 90 wt% n-heptane solution for 30 seconds to initiate interfacial polymerization, to which 0.1 g of trimesoyl chloride and 0.06 g of ferric acetylacetonate were also added. After interfacial polymerization, it was washed with 0.03% NN dimethylformamide ethanol solution. Finally, the membrane was heat treated at 80°C for 5 minutes to obtain an aromatic polyamide composite reverse osmosis membrane.
[0042] The TOC and rejection rate of the composite reverse osmosis membrane were tested by filtering a 200 μg / L aqueous solution of ethyl paraben at 15.5 bar and 25° C. to be 1.83 mg / L and 87.03%, respectively.
[0043] Example 4
[0044] The surface of the base membrane was immersed in the aqueous solution for 60 seconds to allow the base membrane to be fully infiltrated by the aqueous solution. Subsequently, the solution was poured off. Next, after ensuring that there was no visible liquid on the membrane surface, the membrane surface was immersed in a 100 mL mixed solution of 10 wt% dichloromethane and 90 wt% n-heptane solution for 30 seconds to initiate interfacial polymerization, to which 0.1 g of trimesoyl chloride and 0.01 g of ferric acetylacetonate were also added. After interfacial polymerization, it was washed with 0.03% NN dimethylformamide ethanol solution. Finally, the membrane was heat treated at 80°C for 5 minutes to obtain an aromatic polyamide composite reverse osmosis membrane.
[0045] The TOC and rejection rate of the composite reverse osmosis membrane were tested by filtering a 200 μg / L aqueous solution of ethyl paraben at 15.5 bar and 25° C. to be 1.99 mg / L and 86.31%, respectively.
[0046] Comparative Example 1
[0047] The surface of the base membrane was immersed in the aqueous solution for 60 seconds to allow the base membrane to be fully infiltrated by the aqueous solution. Subsequently, the solution was poured off. Next, after ensuring that there was no visible liquid on the membrane surface, the membrane surface was immersed in a solution containing 0.1% trimesoyl chloride, 10% dichloromethane and 90% n-heptane for 30 seconds to initiate interfacial polymerization. It was then washed with 0.03% NN dimethylformamide ethanol solution. Finally, the membrane was heat treated at 80°C for 5 minutes to obtain an aromatic polyamide composite reverse osmosis membrane.
[0048] The composite reverse osmosis membrane flux and rejection rate were 2.86 mg / L and 80.28% respectively when a 200 μg / L aqueous solution of ethyl paraben was filtered at 15.5 bar and 25° C.
[0049] The following figure can be obtained from the experimental data. The results show that the rejection rate of organic micropollutants by the reverse osmosis membrane with 0.03% Fe is greater than that of the reverse osmosis membrane with 0.01% Fe, which is greater than that of the reverse osmosis membrane without iron. As can be seen from the figure, after the three-hour filtration process stabilizes, the rejection rate of the membrane with acetylacetonate iron as the oil phase additive is much greater than that of the membrane without acetylacetonate iron (increased by 10%-12%), and the performance of the reverse osmosis membrane with 0.03% acetylacetonate iron is slightly better than that of the reverse osmosis membrane with 0.01% acetylacetonate iron (increased by 2%). In short, the use of acetylacetonate iron as an organic oil phase additive to prepare a polyamide reverse osmosis membrane can significantly improve the interception effect of the membrane on organic micropollutants, and can improve the ability of the prepared reverse osmosis membrane to filter organic micropollutants.
[0050] Example 5
[0051] The surface of the base membrane was immersed in the aqueous solution for 50 seconds to allow the base membrane to be fully infiltrated by the aqueous solution. Subsequently, the solution was poured off. Next, after ensuring that there was no visible liquid on the membrane surface, the membrane surface was immersed in a 100 mL mixed solution of 10 wt% dichloromethane and 90 wt% n-heptane solution for 30 seconds to initiate interfacial polymerization, to which 0.1 g of trimesoyl chloride and 0.02 g of ferric acetylacetonate were also added. After interfacial polymerization, it was washed with 0.03% NN dimethylformamide ethanol solution. Finally, the membrane was heat treated at 60°C for 7 minutes to obtain an aromatic polyamide composite reverse osmosis membrane.
[0052] Example 6
[0053] The surface of the base membrane was immersed in the aqueous solution for 60 seconds to allow the base membrane to be fully infiltrated by the aqueous solution. Subsequently, the solution was poured off. Next, after ensuring that there was no visible liquid on the membrane surface, the membrane surface was immersed in a 100 mL mixed solution of 10 wt% dichloromethane and 90 wt% n-heptane solution for 30 seconds to initiate interfacial polymerization, to which 0.1 g of trimesoyl chloride and 0.01 g of ferric acetylacetonate were also added. After interfacial polymerization, it was washed with 0.03% NN dimethylformamide ethanol solution. Finally, the membrane was heat treated at 70°C for 6 minutes to obtain an aromatic polyamide composite reverse osmosis membrane.
[0054] Example 7
[0055] The surface of the base membrane was immersed in the aqueous solution for 60 seconds to allow the base membrane to be fully infiltrated by the aqueous solution. Subsequently, the solution was poured off. Next, after ensuring that there was no visible liquid on the membrane surface, the membrane surface was immersed in a 100 mL mixed solution of 10 wt% dichloromethane and 90 wt% n-heptane solution for 30 seconds to initiate interfacial polymerization, to which 0.1 g of trimesoyl chloride and 0.01 g of ferric acetylacetonate were also added. After interfacial polymerization, it was washed with 0.03% NN dimethylformamide ethanol solution. Finally, the membrane was heat treated at 90 ° C for 4 minutes to obtain an aromatic polyamide composite reverse osmosis membrane.
[0056] Example 8
[0057] The surface of the base membrane was immersed in the aqueous solution for 60 seconds to allow the base membrane to be fully infiltrated by the aqueous solution. Subsequently, the solution was poured off. Next, after ensuring that there was no visible liquid on the membrane surface, the membrane surface was immersed in a 100 mL mixed solution of 10 wt% dichloromethane and 90 wt% n-heptane solution for 30 seconds to initiate interfacial polymerization, to which 0.1 g of trimesoyl chloride and 0.01 g of ferric acetylacetonate were also added. After interfacial polymerization, it was washed with 0.03% NN dimethylformamide ethanol solution. Finally, the membrane was heat treated at 100 ° C for 3 minutes to obtain an aromatic polyamide composite reverse osmosis membrane.
[0058] Example 9
[0059] The surface of the base membrane was immersed in the aqueous solution for 60 seconds to allow the base membrane to be fully infiltrated by the aqueous solution. Subsequently, the solution was poured off. Next, after ensuring that there was no visible liquid on the membrane surface, the membrane surface was immersed in a 100 mL mixed solution of 10 wt% dichloromethane and 90 wt% n-heptane solution for 30 seconds to initiate interfacial polymerization, to which 0.1 g of trimesoyl chloride and 0.01 g of ferric acetylacetonate were also added. After interfacial polymerization, it was washed with 0.03% NN dimethylformamide ethanol solution. Finally, the membrane was heat treated at 75 ° C for 5 minutes to obtain an aromatic polyamide composite reverse osmosis membrane.
[0060] Example 10
[0061] The surface of the base membrane was immersed in the aqueous solution for 60 seconds to allow the base membrane to be fully infiltrated by the aqueous solution. Subsequently, the solution was poured off. Next, after ensuring that there was no visible liquid on the membrane surface, the membrane surface was immersed in a 100 mL mixed solution of 10 wt% dichloromethane and 90 wt% n-heptane solution for 30 seconds to initiate interfacial polymerization, to which 0.1 g of trimesoyl chloride and 0.01 g of ferric acetylacetonate were also added. After interfacial polymerization, it was washed with 0.03% NN dimethylformamide ethanol solution. Finally, the membrane was heat treated at 65 ° C for 4 minutes to obtain an aromatic polyamide composite reverse osmosis membrane.
[0062] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. An application based on iron acetylacetonate polyamide membrane, characterized in that: The polyamide membrane based on ferric acetylacetonate is used to remove organic micropollutants, and the organic micropollutants are ethylparaben; The preparation process of the ferric acetylacetonate polyamide film comprises the following steps: Step 1, soaking the basement membrane in an aqueous solution to form a process basement membrane 1; The aqueous phase solution is a mixed solution containing camphorsulfonic acid, triethylamine and m-phenylenediamine; the mass fractions of camphorsulfonic acid, triethylamine and m-phenylenediamine in the aqueous phase solution are 2.6%, 1.1% and 3% respectively; Step 2, immersing the process base film 1 in an organic phase solution to cause an interfacial polymerization reaction to form a process base film 2; the organic phase solution is composed of 10% dichloromethane and 90% n-heptane solution by mass fraction, and trimesoyl chloride and ferric acetylacetonate are also added to the organic phase solution; In step 2, 0.1 g of trimesoyl chloride was added to 100 mL of the organic phase solution; In step 2, 0.01 g to 0.06 g of ferric acetylacetonate is added to 100 mL of the organic phase solution; Step 3, cleaning the second process base film and then heat treating it to obtain a polyamide film.
2. The use of a polyamide film based on iron acetylacetonate according to claim 1, characterized in that: In step 1, the base film is immersed in the aqueous solution for 10 to 60 seconds.
3. The use of a polyamide film based on ferric acetylacetonate according to claim 1, characterized in that: In step 2, the immersion time of the process base membrane 1 in the organic phase solution is 10 to 50 seconds.
4. The use of a polyamide film based on ferric acetylacetonate according to claim 1, characterized in that: In step 3, the base film 2 is cleaned by using an ethanol solution containing N-N-dimethylformamide.
5. The use of a polyamide film based on iron acetylacetonate according to claim 1, characterized in that: The heat treatment temperature is 60-100°C, and the heat treatment time is 3-7 minutes.
Citation Information
Patent Citations
Decolorizing membrane and preparation method and application thereof
CN112535955A